2019
DOI: 10.1136/vetreccr-2019-000817
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous regression of a cervical intervertebral disc extrusion in French bulldogs documented on MRI after medical management

Abstract: Spontaneous regression of cervical intervertebral disc extrusion (cIVDE) has been reported in people. It has also been reported in a dog after four months of medical management. Two French bulldogs were presented to two different referral centres for signs of neck pain or myoclonic twitching. Both were diagnosed with cIVDE on MRI and were managed medically. One dog re-presented after six weeks with recurrent signs while it was still being strictly rested. Repeat MRI showed a new disc extrusion with apparent sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Raimondi et al 9 documented spontaneous resorption of a C3-C4 IVDE in a cocker spaniel, confirmed via high-field MRI following 4 months of conservative therapy. Similarly, Argent et al 10 reported two French bulldogs of which spontaneous resorption of a c-IVDE was documented on follow-up MRI. One case with a spontaneously resorbed C3-C4 IVDE, and the other with a spontaneously resorbed C4-C5 IVDE were documented on follow-up MRI 5 weeks and 4 months following conservative therapy, respectively.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Raimondi et al 9 documented spontaneous resorption of a C3-C4 IVDE in a cocker spaniel, confirmed via high-field MRI following 4 months of conservative therapy. Similarly, Argent et al 10 reported two French bulldogs of which spontaneous resorption of a c-IVDE was documented on follow-up MRI. One case with a spontaneously resorbed C3-C4 IVDE, and the other with a spontaneously resorbed C4-C5 IVDE were documented on follow-up MRI 5 weeks and 4 months following conservative therapy, respectively.…”
Section: Discussionmentioning
confidence: 81%
“…documented spontaneous resorption of a C3–C4 IVDE in a cocker spaniel, confirmed via high‐field MRI following 4 months of conservative therapy. Similarly, Argent et al 10 . reported two French bulldogs of which spontaneous resorption of a c‐IVDE was documented on follow‐up MRI.…”
Section: Discussionmentioning
confidence: 84%